Body score in relation to fertility of Sahiwal x Friesian dairy cows - Jamaludin, Rafidah; Sharifuddin, W.; Jainudeen, Mohamed Razeen (Malaysian Society of Applied Biology, 1983)
One hundred and seventeen lactating Sahiwal x Friesian F1 cows from inistitutional and small holder farms were studied to establish a body scoring system and to estimate body weight from heart girth measurements. Body weight and heart girth measurement in 47 lactating and non-lactating cows showed that there was a close relationship (r = 0.944). The regression equation detennined was y .. -688 + 6.41x²• where y is the predicted body weight (kg) and x is the heart girth (cm). A body scoring system (1-7) was developed based on the quantity of subcutaneous fat covering lumbar vertebra, spinous processes, tuber ischi, tuber coxae and ribs. The mean body score for fertile cows (4.7 + 1.27) was significantly higher (p (0.05) than for infertile cows (3.8 + 1.67). The mean body score of 3.03 + 0.81 for cows belonging to small holders was due to the low level of nutrition and management. Lactating cows on experimental diets. based on ad lib grazing or 30 kg fodder and at least 3 to 5 kg of concentrate mixture daily, achieved a body score of 4 and above.